Hydatid cyst of ovary: an unusual site - Goyal, Neha A.; Vaidya, Ritu R.; Zaidi, Sarah H.; Gandhewar, Manisha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Discovering a hydatid cyst in pelvic region, especially as primary localization, is a rare event; as a matter of fact according to data provided by literature the incidence is between 0.2 and 2.25%. The ovarian involvement is often secondary to a cyst's dissemination localized in a different site. When possible the optimal treatment is represented by radical laparotomic cystectomy. We report a case of an old postmenopausal woman presented with intermittent dull aching pain with 16 weeks cystic pelvic mass which mimicked the ovarian malignancy even after imaging techniques. We treated the case with laprotomic cystectomy